GE_GERICHTE P/23634/2020 vom 22. Mai 2023 - GE Cour de justice (2023)
MEURTRE;HOMICIDE PAR NÉGLIGENCE;MESURE THÉRAPEUTIQUE INSTITUTIONNELLE;EXPULSION(DROIT PÉNAL) | CP.111; CP.117; CP.59; CP.66a.al1.letb